Impact Of Female School Teachers’ Dress Code on Job Performances: A Cross-Sectional Study in Saga City, Japan - U.G.L.B. Jayasooriya; Saliya De Silva; Wanigasundera Appuhamillage Don Padmasiri Wanigasundera (Indonesian Journal of Social Research (IJSR), 2020)
The dress is an integral part of a profession. The research focuses on the dress codes of school teachers in Japan. Japan has relaxed the dress norms of school teachers over the years from a traditional/formal dress to a casual dress. We intended to examine if this change has a significant effect on the self-perceived job performance among school teachers in Japan with the purpose of seeking recommendations for many Asian countries like Sri Lanka in which traditional dress norms applied to teachers have not changed much or at all. A combined qualitative and quantitative study was conducted with three chosen prefectural schools in the Saga city, Japan. The qualitative study was a thematic analysis based on in-depth interviews with five selected school teachers. The quantitative study (n=30) was a descriptive cross-sectional study. A culturally validated, self-administered questionnaire was used to collect data on socio- demographic characteristics and dress code from the study sample. Self-perceived comfort level and effect of the dress code on performing their jobs were assessed on a set of given scenarios related to their profession. The responses were recorded on a five-point Likert scale. The subjects aged from 26 to 61 years old (mean =44±8 years). Wilcoxon Signed- Rank test indicated that the self-reported mean comfort score for casual dress of 25.75 is significantly higher than that of Kimono (mean score =10.77, p=.000). Most respondents believed that their job performance could be affected by the way they dress. According to the in-depth interviews, it was revealed that, compared to the traditional Kimono, the casual dress is convenient and comfortable for the duties they perform. Thus, the study reveals that Japan sets an example for the countries that are more concerned about embodying cultural symbols in the appearance of teachers rather than their convenience and efficiency: Japan has been successful in relaxing dress norms while sustaining the quality of education and cultural values.